Neuropati Optik Toksik Akut - Setyandriana, Yunani (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2009)
The aim of the study was to report a case of acute toxic optic neuropathy. A case report of a 29 years old female with acute visual loss in both eyes. There was history of taking multiple drugs about 4 days while in the hospital. We performed visual acuities examination, light projection, color perception, funduscopy, and visual field examinations. The visual acuities were 1/300 on both eyes with bad color perceptions, the other examination were normal. Visual field examination was performed on the third day when the visual acuities were improved, showing severe depression on the both eyes and diagnosed acute toxic optic neuropathy. She is given neurotropic injection once daily, neutotropic tablet twice daily, and acetazolamide tablet 3 times daily. Retrobulber dexamethason injection on second day for 5 days, and continued with dexamethason tablet 1mg four times daily. The patients was consulted to neurology, ENT, internist, and oral medicine department. The visual acuity became better 3/60 in the both eyes on the third days, on the seventh days on the right eye 5/60 and the left eye 4/60. One week later, the visual acuity became 6/12 on the right eye and 6/15 on the left eye, but there was color deficiency in both eyes. Visual field examination of both eyes showed improvement to be moderate depression. The treatment was continued and dexamethason was tapering off. Follow up in one month the visual acuity improved to be 6/7.5 on the right eye and 6/8.5 on the left eye, although there was still green color blind with one eye. Visual field showed mild depression. Concluded a case of acute toxic optic neuropathy treated with steroid injection and orally, and neurotropic agents, there was a good result although not fully recovery.Tujuan penulisan makalah ini adalah untuk melaporkan laporan kasus yaitu neuropati optic toksik akut. Dilaporkan kasus seorang wanita 29 tahun buta mendadak kedua matanya. Empat hari sebelum datang ke rumah sakit minum beberapa obat. Dilakukan pemeriksaan visus, proyeksi cahaya, persepsi warna, funduskopi, dan lapang pandang. Visus kedua mata 1/300 dengan persepsi warna buruk, pemeriksaan lain normal. Pemeriksaan lapang pandang dilakukan hari ke-3 saat visusnya mulai membaik. Hasilnya menunjukkan depresi berat kedua mata dan didiagnosis neuropati optic toksik akut. Diberikan terapi neurotropik injeksi sekali sehari, neurotropik tablet 2x sehari, dan asetazolamide tablet 3x sehari. Dexamethason injeksi retrobulber diberikan hari kedua selama 5 hari, dilanjutkan dengan dexamethason tablet 1mg 4x sehari. Pasien dikonsulkan ke neurologi, THT, penyakit dalam, dan dokter gigi. Visus hari ketiga membaik menjadi 3/60 pada kedua mata, hari ke- 7 menjadi 5/60 mata kanan dan 4/60 mata kiri, namun didapatkan buta warna pada kedua mata. Seminggu kemudian visus membaik menjadi 6/12 mata kanan dan 6/15 mata kiri. Lapang pandang menunjukkan depresi sedang. Terapi diteruskan dengan dexamethason tablet diturunkan dosisnya. Follow up 1 bulan kemudian menunjukkan perbaikan dengan visus 6/7.5 mata kanan dan 6/8.5 mata kiri, namun masih terdapat buta warna hijau. Pemeriksaan lapang pandang menunjukkan depresi ringan. Disimpulkan bahwa kasus neuropati optic toksik akut diterapi dengan steroid injeksi dan oral serta obat neurotropik, didapatkan perbaikan kondisi meskipun tidak sempurna.